2018
DOI: 10.1016/j.ekir.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Acting Oral Anticoagulants as Prophylaxis Against Thromboembolism in the Nephrotic Syndrome

Abstract: We report 2 cases of apixaban use as prophylaxis against thromboembolism in the nephrotic syndrome (NS), and review the existing literature on direct-acting oral anticoagulant (DOAC) use in this scenario. Our cases appear to be the first reported use of apixaban as prophylaxis against thromboembolism in NS. We report our systematic review of the existing literature on direct-acting oral anticoagulant (DOAC) use in NS, and discuss theoretical issues relevant to their therapeutic use in this clinical scenario. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 54 publications
0
28
0
3
Order By: Relevance
“…Apixaban use was recently described for 2 patients with NS. 56 One had minimal change disease and was treated with prophylactic apixaban until remission. The second had MN with a remote history of VTE and received apixaban prophylaxis for 3 months until resolution of NS.…”
Section: Anticoagulation Scenarios In Kidney Diseasementioning
confidence: 99%
“…Apixaban use was recently described for 2 patients with NS. 56 One had minimal change disease and was treated with prophylactic apixaban until remission. The second had MN with a remote history of VTE and received apixaban prophylaxis for 3 months until resolution of NS.…”
Section: Anticoagulation Scenarios In Kidney Diseasementioning
confidence: 99%
“…Notably, apixaban and rivaroxaban are highly bound to plasma proteins (87, 90% ~ 95%) in humans, and serum albumin is the main binding component. If these drugs are considered for patients with hypoalbuminemia, the protein binding rate is an important consideration in primary MN [45, 46]. At present, although no pharmacokinetic study was available and no clinical trial had been performed in primary MN, some case reports reported the successful use of DOACs for the treatment of clinically evident thrombosis or thromboprophylaxis in primary MN [46].…”
Section: Results: Prevention Of Thrombogenesis and The Anticoagulant mentioning
confidence: 99%
“…The use of direct oral anticoagulants in NS or APS is controversial, and it is not generally recommended as previous trials were associated with more vascular events compared to that of warfarin, and with limited evidence, further studies are warranted [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%